MEMBANGUN KEMANDIRIAN FINANCIAL ANAK PANTIASUHAN MELALUI PELATIHAN KEWIRAUSAHAAN - isbanah, yuyun; Kautsar, Achmad; Prabowo, Prayudi Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2017)
The purpose of entrepreneurship training is to increase intention, motivation, and entrepreneurship skills to the orphanage children. An Orphanage girl is selection as training objects because they need to have the skills to train their own souls. Entrepreneurship training is aim to training financial independence early on. Entrepreneurship training and making beads brooch located at Al-Chusnaini SidoarjoÂ Orphanage, which followed by 34 participants consisting of young women and administrators of orphanages. The method of implementation is used two steps. The first step is entrepreneurship learning and the second step is the workshop of making beads brooch. This training goes as expected. The results of the questionnaire indicate that generally, the training is able to understand by the participants. Most of the participants thought that training were able to increase their skills, and there was an increase in entrepreneurship intention. Keywords: financial independence, orphanage, entrepreneur intention